The issue of consent in rape cases / Abd Rahim Osman - Osman, Abd Rahim (Faculty of Law, 1986)
This paper is inspired by the everyday happenings of cases read in the newspaper.Rape being most common of violence against woman, is not just sex. Rape is not shown as an ugly violent act in phonography, but the woman is depicted as eventually enjoying it and behind her cries are supposedly the moans of enjoyment and acceptance. The reasons for rape are almost seen as due to the woman; her attire, her courage to walk at night and other instances including morality are used to prove consent on her part. Further, in the eyes of society, if an unmarried woman is raped and if it is found out that she is not a virgin at the time of the alleged rape, there will be almost automatic inclination to think that perhaps she consented. It is due to this injustice( if the writer may say ), that has led the writer to examine the state of the present law and to make, if possible appropriate proposals and suggestions .The writer feels that the state of the present law is not balanced in that it does not confer sufficient protection to the victim, leading normally, the woman holds back the charges and refuses to report the case resulting the offender usually get away scot-free.This therefore, should be putt-off as history and not as a present happenning in a civilised society today.